Evaluasi Kesesuaian Sarana dan Prasarana Studio Gambar Teknik Pemesinan Kapal Sekolah Menengah Kejuruan Terhadap Standar Nasional Pendidikan - Putra Nanda Rizki Abditiya; Ari Dwi Nur Indriawan Musyono (Jurnal Muara Pendidikan, 2026)
The availability of technical drawing studio facilities and infrastructure that meet standards is an important factor in supporting competency-based learning in vocational education. However, empirical studies that specifically evaluate the suitability of Ship Machining Technical Drawing studios to national regulations are still limited. This study aims to evaluate the level of suitability of the facilities and infrastructure of the Ship Machining Engineering Drawing Studio at SMK Negeri 10 Semarang against the National Education Standards. The study uses a descriptive method with a quantitative approach. Data were collected through closed questionnaires, observations, and documentation, with respondents being 12th grade students who actively use the drawing studio. The instruments were compiled based on the indicators of Permendiknas No. 40 of 2008, Permendiknas No. 24 of 2007, and Indonesian National Standards (SNI), and analyzed using percentage techniques. The results showed that the level of conformity of facilities and infrastructure was 78.22%, which was in the high category but still at the lower limit of that category. These findings indicate that the drawing studio facilities have met the minimum functional standards but are not yet fully optimal in technical aspects such as lighting, ventilation, and work safety. The implications of this study emphasize the need for periodic evaluation of facilities and infrastructure as well as facility management policies oriented toward improving the quality of practical learning in vocational schools.